Evaluation and management of obstetric genital fistulas treated at a pelvic floor centre in Germany - Christl Reisenauer; Bastian Amend; Claudius Falch; Harald Abele; Sara Yvonne Brucker; Jürgen Andress (BMC, 2021)
Abstract Background Obstetric genital fistulas are an uncommon condition in developed countries. We evaluated their causes and management in women treated at a German pelvic floor centre. Methods Women who had undergone surgery for obstetric genital fistulas between January 2006 and June 2020 were identified, and their records were reviewed retrospectively. Results Eleven out of 40 women presented with genitourinary fistulas, and 29 suffered from rectovaginal fistulas. In our cohort, genitourinary fistulas were more common in multiparous women (9/11), and rectovaginal fistulas were more common in primiparous women (24/29). The majority of the genitourinary fistulas were at a high anterior position in the vagina, and all rectovaginal fistulas were at a low posterior position. While all genitourinary fistulas were successfully closed, rectovaginal fistula closure was achieved in 88.65% of cases. Women who suffered from rectovaginal fistulas and were at high risk of recurrence or postoperative functional discomfort and desired another child, we recommended fistula repair in the context of a subsequent delivery. For the first time, pregnancy-related changes in the vaginal wall were used to optimize the success rate of fistula closure. Conclusions In developed countries, birth itself can lead to injury-related genital fistulas. As fistula repair lacks evidence-based guidance, management must be tailored to the underlying pathology and the surgeon's experience. Attention should be directed towards preventive obstetric practice and adequate perinatal and postpartum care. Although vesicovaginal fistulas occur rarely, in case of urinary incontinence after delivery, attention should be paid to the patient, and a vesicovaginal fistula should be ruled out. Trial registration Retrospectively registered, DRKS 00022543, 28.07.2020.